Influence of the reducing agents on morphology and properties of silver structures on paper - Thi Bich Ngoc, Nguyen; Thi Thuy, Nguyen; Trong Nghia, Nguyen; Duc Toan, Nguyen; Dao Duc Manh; Viet Ha, Chu; Thi Ha Lien, Nghiem (Vietnam Journal of Science and Technology, 2024)
Paper-based SERS substrates (PSSs) with tunable plasmonic properties and excellent flexibility have been applied in various fields. These SERS substrates were prepared using a direct chemical reduction synthesis method for the present work. By using various types of reducing agents (RAs): (1) sodium borohydride (NaBH4), (2) ascorbic acid (L-AA), (3) glucose, and (4) formaldehyde (HCHO), the silver nanostructures (AgNS) on cellulose paper fiber was fabricated with the morphologies. Morphological research results have shown that with strong RAs, AgNS on paper substrates have a spherical shape. In contrast, with weak RAs, ANS on paper substrates have an anisotropic morphology which depends on the crystal surface development priority. Specifically, AgNS generated on paper using glucose have a bar shape and thin planar silvery-wing shape when using the reducing agent L-AA. The plasmon characterization of AgNS on paper was systematically investigated by the diffuse reflectance spectroscopy. The fabricated paper-based SERS substrates were used to detect melamine in an aqueous solution and to determine the influence of type RAs on the enhancement factor (EF) and signal uniformity of SERS substrates. Among the four types of RAs, the SERS substrates used NaBH4 have the highest SERS signal with the limit of detection of 10-8 M for melamine and the EF = 2.3 × 109.